Modeling of starchy melts expansion by extrusion. (February 2016) - Kristiawan, M.; Chaunier, L.; Della Valle, G.; Ndiaye, A.; Vergnes, B.
Abstract: Background: Expansion phenomenon is a key-point of the development of extruded starchy foods. Despite the huge number of studies, the complexity of the phenomenon still challenges its modeling. Current available models based on continuum mechanics are still too complex to be coupled with any 1D extrusion model available, in order to predict the density and the cellular structure of the starchy foams. Scope and approach: In this paper, the different modeling approaches for vapor expansion are reviewed. Then, a survey of the different mechanisms (bubbles nucleation, growth, coalescence, shrinkage and setting), using qualitative knowledge representation and reasoning, allows to improve the understanding of the effect of extrusion variables (temperature, moisture content, die geometry …) and material rheological properties on the expansion phenomenon. Based on experimental results reported in the literature, a phenomenological model of expansion can then be suggested. Key findings and conclusions: The knowledge representation and reasoning leads to a concept map of the causal influences between input, physical mechanisms and output variables. The phenomenological model would allow to predict output variables characterizing foam macrostructure (bulk expansion indices and anisotropy factor) and cellular fineness based on X-ray tomography measurements. A scale down from macrostructure to cellular structure could be achieved by establishing a link between anisotropy factor and cellular fineness. Once validated, this model could be coupled with any 1D extrusion model in order to build a global model for the design of cereal-based extruded foods. Highlights: A concept map relates extrusion variables and material properties to expansion characteristics. The importance of elongational properties and their relation to storage modulus are stated. A phenomenological model of expansion, including storage modulus, is proposed. Anisotropy mapping shows that radial expansion favors coarse cellular structures. Structure scale-down is achieved by relating cell fineness to anisotropy factor.